PEMANFAATAN EKSTRAK NABATI UNTUK MENINGKATKAN KUALITAS HASIL PANEN TANAMAN SAWI - Marliana S. Palad; Aminah Muchdar (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
The study aims to determine the effect of the provision of vegetable extracts on the quality and quantity of mustard crop yields, which was carried out in Malino, Gowa Regency, with a research period of 4 months, from March to July 2009. The research was conducted in the form of experiments arranged according to a randomized design Group (RBD) with five treatments and each treatment had 4 replications, so there were 20 experimental plots.Based on the results of the study, that plants that have economic value in the field can be used as a vegetable pesticide substitute for chemical pesticides to control plant pests, so as to suppress pest populations and reduce leaf defects by applying vegetable extracts at concentrations of 4 or 6 cc/liter of water with an interval of giving once a week. Application of vegetable extract with more doses the concentration can improve the quality and quantity of mustard greens with growth and yield of higher yields which is an average of 407.5 grams in the treatment of 6 cc/liter of water (E3).